Breast surgical techniques and interdisciplinary management - Scott-Conner, Carol E. H.; Dirbas, Frederick; SpringerLink (Online service). (New York Springer, 2011)
This comprehensive manual on breast disease deals with all aspects of the surgical management of both benign and malignant disease. The chapters are written by leading experts, clearly illustrated with line drawings, clinical photos and diagnostic radiology images. Breast Surgery is divided into sections following the patterns of patient management from diagnosis through treatment and reconstruction. Part One, "Fundamentals", addresses common aspects of working with breast cancer patients and understanding the members of the breast cancer team. Part Two is an overview of "Biologic Principles". Parts Three, Four, and Five review "The Initial Evaluation", "Common Presenting Problems", and "Diagnostic Techniques". Part Six, an overview of breast cancer treatment, includes chapters on "Breast Cancer Staging", "Introduction to Gene Expression Profiling", and "Psychological Issues". Part's Seven through Twelve deal with important aspects of breast surgery and interdisciplinary care including pathology, medical oncology, and radiation oncology, with several chapters on neoadjuvant therapy and partial breast irradiation. Part Thirteen includes many chapters on followup of the breast cancer survivor, including late changes on physical exam and imaging, local recurrence, and treating metastatic disease. Though not intended to replace a text reference, Breast Surgical Disease and Interdisciplinary Management offers a comprehensive guide to provide practical advice for those seeking concise, expert input that can be quickly accessed on multiple topics associated with the care of the breast cancer patient.
Foreword -- Section One-Fundamentals -- Professionalism in the Approach to the Patient -- The Clinical Breast Cancer Team -- The Role of the Specialist Breast Nurse -- Social Work and Breast Cancer Care -- Reducing Medical Malpractice Risk in Breast Cancer Care: A Surgical Perspective -- Career Development for Breast Surgical Oncology -- Successful Management of a Breast Surgery Practice -- Section Two-Biologic Principles -- Normal Morphology, Physiological Changes, and Benign Breast Disease -- The Biology of Breast Cancer -- Section Three-Initial Evaluation of the Patient -- Obtaining a History and Performing the Clinical Breast Examination -- Primer on Ultrasound for the Breast Surgeon -- The Complete Radiology Workup -- Section Four-Common Presenting Complaints and Concerns -- Identification and Management of Women at High Familial Risk for Breast Cancer -- Clinical Management of Breast Pain -- Breast Mass -- Breast Infection -- The Evaluation and Treatment of Nipple Discharge -- Gynecomastia -- The Effects of Menopausal Hormone Therapy on Breast Cancer: Evidence from the Women?s Health Initiative Randomized Placebo-Controlled Trials -- Section Five-Diagnostic Techniques -- Office Diagnostic Procedures -- Image-Guided Breast Biopsy -- Breast Biopsy Techniques -- Mammary Ductoscopy -- Section Six - Breast Cancer Overview -- Assessment Of Extent Of Disease In Primary Breast Cancer -- Breast Cancer Staging: Predicting Outcome and Response to Treatment -- Breast Cancer Treatment Guidelines -- Introduction to Gene Expression Profiling in Breast Cancer -- Clinical Trial Overview and Enrollment -- Psychiatric and Psychological Issues -- Fertility Issues for Newly Diagnosed Women Interested in Child Bearing ? Strategies and Options -- Section Seven - Breast Surgery ? Management of the Primary Tumor -- Regional Anesthesia for Breast Surgery -- Lumpectomy -- Oncoplastic Techniques for Breast Conservation Surgery -- Ablative Techniques -- Mastectomy -- Nipple and Areola-Sparing Mastectomy -- Integration of Neoadjuvant Systemic Therapy Into Surgical Practice -- Oncologic Breast Reconstruction: Principles and Practice -- Section Eight - Breast Surgery ? Sentinel Node Biopsy and Axillary Dissection -- Sentinel Lymph Node Biopsy?an Overview -- Sentinel Lymph Node Biopsy: Radiotracer Technique at Memorial Sloan-Kettering Cancer Center -- Sentinel Node Biopsy Using Lymphazurin -- The Use of Methylene Blue as a Tracer Agent in Sentinel Lymph Node Biopsy -- Axillary Lymph Node Dissection -- Section Nine - Breast Surgery ? Special Issues -- Evaluation and Management of Women Presenting with Breast Symptoms During Pregnancy -- Paget?s Disease Of The Breast -- Male Breast Cancer -- Breast Sarcomas -- Axillary Metastases with Unknown Primary -- Section Ten - Cytology and Pathology -- Breast Cytology -- The Breast Pathology Report -- Risk Lesions of the Breast: Usual Ductal Hyperplasia, Atypical Ductal Hyperplasia, Lobular Neoplasia, and the Spectrum of Columnar Cell Alterations -- Duct Carcinoma In Situ ? a Gordian Knot Untied -- Pathology: Invasive Carcinoma -- Interpreting Breast Pathology in the Setting of Neoadjuvant Chemotherapy -- Pathology of Sentinel Lymph Nodes and Axillary Nodes -- Selected Fibroepithelial, Mesenchymal and Hematolymphoid Tumors of the Breast -- Banking tissue specimens for research -- Section Eleven - Systemic Therapy for Breast Cancer -- Basic Principles of Anti-Neoplastic Therapies -- Neoadjuvant Endocrine Therapy in the Treatment of Early-Stage Breast Cancer -- Neoadjuvant Systemic Therapy For Breast Cancer -- Adjuvant Systemic Therapy -- Adjuvant Endocrine Therapy -- Systemic Treatment During Pregnancy -- Breast Cancer in the Elderly -- Complementary and Alternative Medicine in Breast Cancer -- Section Twelve - Radiation Therapy of the Breast -- Basic Principles Of Radiobiology -- Whole Breast Radiotherapy -- Accelerated, Partial Breast Irradiation Overview -- PBI: Brachytherapy Techniques -- Accelerated Partial Breast Irradiation: Balloon Catheter Brachytherapy -- APBI 3D Conformal External Beam - The NYU Technique -- Accelerated, Partial Breast Irradiation with Intraoperative Radiotherapy -- Post-Mastectomy Radiation Therapy -- Regional Nodal Radiation as an Alternative to Surgery -- Controversial Indications For Breast Conserving Therapy And Radiation -- Section Thirteen - The Breast Cancer Survivor -- Survivorship -- Follow-up Strategies After Breast Cancer Treatment -- Pregnancy After Breast Cancer -- The Potential of the Electronic Health Record in the Breast Center -- Clinical Breast Examination After Treatment of Breast Cancer -- Breast Imaging Following Breast Conservation Therapy -- Detection and Management of Ipsilateral Breast Cancer Recurrence -- Lumpectomy or Mastectomy in Patients Presenting with Metastatic Disease -- Managing Breast Cancer- Associated Lymphedema -- Chronic Pain After Surgery for Breast Cancer -- Systemic Treatment Of Metastatic Breast Cancer.
Electronic reproduction.
Keywords: Breast -- Surgery; Breast -- Diseases -- Treatment; Electronic books